Assessment of lignocellulosic residues from Northern Patagonian Andes (Argentina) for cultivation of Pleurotus ostreatus - Maximiliano Rugolo; Juan Manuel Roggero Luque; Mario Rajchenberg; Carolina Barroetaveña (Universitas Scientiarum)
This work evaluated mycelial growth rate (Kr) and fruiting of two Pleurotus ostreatus commercial strains (A01, 129) on formulations composed of lignocellulosic residues from farming and agroindustry of Northern Patagonian Andes, and of woody materials from invasive plants. Rosehip fluffs (RF), rosehip woodchips (RWC), southern beech wood shavings (SBWS), wheat straw (WS), and willow woodchips (WWC) were used as base substrates, and brewing bagasse (BB) as an alternative supplement to wheat bran (WB). Kr was higher in WS-WB and WS-BB for both strains. Experiments in fruiting chambers showed biological efficiencies (BEs) above 40% in WS-BB (both strains) and WS-WB (strain 129). Formulations using RWC or WWC gave BEs under 40%, while those composed of SBWS or RF showed lower Kr and contamination by moulds. Medium-scale fruiting experiments using strain A01 showed the highest BEs in WS-BB and RWC-WB. These results suggest that WS is the best substrate for Pleurotus ostreatus culture, although scarce in Northern Patagonian Andes. Nevertheless, WWC and RWC are suggested as alternative substrates, while BB is cheap and abundant, suitable as an alternative supplement to WB.